Cutaneous lupus erythematosus: updates on pathogenesis and associations with systemic lupus. Issue 5 (September 2016) - Stannard, Jasmine N.; Kahlenberg, J. Michelle
Abstract : Purpose of review: Cutaneous lupus erythematosus (CLE) is a common manifestation among systemic lupus patients. There are no U.S. Food and Drug Administration approved therapies for CLE, and these lesions are frequently disfiguring and refractory to treatment. The present review will cover the recent inroads made into understanding the mechanisms behind CLE lesions and discuss promising therapeutic developments. Recent findings: The definition of cutaneous lupus is being refined to facilitate diagnostic and research protocols. Research into the pathogenesis of CLE is accelerating, and discoveries are now identifying genetic and epigenetic changes which may predispose to particular disease manifestations. Furthermore, unique features of disease subtypes are being defined. Murine work supports a connection between cutaneous inflammation and systemic lupus disease activity. Importantly, human trials of type I interferon blockade hold promise for improving our treatment armamentarium for refractory CLE lesions. Summary: Continued research to understand the mechanisms driving CLE will provide new methods for prevention and treatment of cutaneous lesions. These improvements may also have important effects on systemic disease activity, and thus, efforts to understand this link should be supported.